2007
DOI: 10.1523/jneurosci.1032-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Activity Patterns in Thermosensory Neurons of Freely Moving Caenorhabditis elegans Encode Spatial Thermal Gradients

Abstract: Our understanding of the operation of neurons and neuronal circuits has come primarily from probing their activity in dissected, anesthetized, or restrained animals. However, the behaviorally relevant operation of neurons and neuronal circuits occurs within intact animals as they freely perform behavioral tasks. The small size and transparency of the nematode Caenorhabditis elegans make it an ideal system for noninvasive, optical measurements of neuronal activity. Here, we use a high signal-to-noise version of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
84
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(88 citation statements)
references
References 22 publications
4
84
0
Order By: Relevance
“…Several classes of GECIs have performed well for neural imaging, encompassing single-FP and FRET sensors, and sensors based on calmodulin and troponin-C calcium-binding domains. Published GECIs are adequate for detecting high frequency bursts of neuronal activity, making them appropriate for activity localization in mouse myotubes (Nakai et al, 2001), mouse cerebellum (Diez-Garcia et al, 2005), or in invertebrate systems (Kerr et al, 2000;Higashijima et al, 2003;Wang et al, 2003;Chronis et al, 2007;Clark et al, 2007). However, reliable in vivo single-AP detection is not yet feasible with the current generation of techniques.…”
Section: Resultsmentioning
confidence: 99%
“…Several classes of GECIs have performed well for neural imaging, encompassing single-FP and FRET sensors, and sensors based on calmodulin and troponin-C calcium-binding domains. Published GECIs are adequate for detecting high frequency bursts of neuronal activity, making them appropriate for activity localization in mouse myotubes (Nakai et al, 2001), mouse cerebellum (Diez-Garcia et al, 2005), or in invertebrate systems (Kerr et al, 2000;Higashijima et al, 2003;Wang et al, 2003;Chronis et al, 2007;Clark et al, 2007). However, reliable in vivo single-AP detection is not yet feasible with the current generation of techniques.…”
Section: Resultsmentioning
confidence: 99%
“…Our goal was to determine whether our setup was capable of finding distinct neuronal activity patterns that correspond to sensory input and motor output. To activate the circuits for thermotaxis in C. elegans, which are most sensitive at temperatures near and above the temperature of cultivation, we cultivated worms at 15°C and subjected them to fluctuations between 15°C and 17.5°C (3,29). To extract general patterns in calcium dynamics across the head ganglia, we performed cluster analysis.…”
Section: Classification and Correlation Of Intracellular Calcium Dynamentioning
confidence: 99%
“…The nematode Caenorhabditis elegans is particularly ideal for optical neurophysiology owing to its small size, optical transparency, compact nervous system, and ease of genetic manipulation. Imaging systems for tracking the activity of small numbers of neurons have been effective in determining their role during nematode locomotion and navigational behaviors like chemotaxis, thermotaxis, and the escape response (1)(2)(3)(4)(5)(6).…”
mentioning
confidence: 99%
“…Calcium imaging of the AFD neuron in response to temperature waveforms has shown that the operating range of AFD spans the range of isothermal tracking and cryophilic behavior. At temperatures near and above the T s , warming will depolarize AFD and cause an increase in intracellular calcium level whereas cooling will hyperpolarize AFD and cause a decrease in the calcium levels (29)(30)(31)(32).…”
Section: Afd Responds To Temperatures That Span Both Negative and Posmentioning
confidence: 99%